Balanced assessment systems revisited - Dávid Dankó; Márk Péter Molnár (Journal of Market Access & Health Policy)
In 2014, balanced assessment systems (BAS) were proposed as a resource-conscious, ‘fit-for-purpose’ form of health technology assessment for middle-income countries which lack resources and competences necessary for resource-intensive health technology assessment models. BAS has undergone extensive policy debate in the period since its publication but it has not been critically assessed in a structured form yet. This article aims to describe both the contributions and the weak spots of the original framework and to reflect on them with the intention of further developing the model.